Limits and Risks in Psychological Care for Prisoners with Mental Disorders - Popa, Ecaterina (New Trends in Psychology, 2024)
The article "Limits and risks in psychological care for prisoners with mental disorders" provides a realistic and straightforward review of the limits and risks faced by prison psychologists in working with prisoners suffering from serious mental disorders. In a crowded prison environment, with competing priorities, there is a danger that people with serious mental disorders may be overlooked and their difficulties go unrecognized. Thus, there are some limits and risks that we are trying to shape so that prison psychologists can provide quality psychological care.